Fourth Primary Malignant Tumor in a Patient with Possible Li-Fraumeni Syndrome: Synchronous Diagnosis of Postirradiation Sarcoma, Cutaneous Relapse of a Previous Soft Tissue Sarcoma, and Lung Adenocarcinoma - Feridun Yumrukçal; Yalin Dirik; Arda Çinar; Levent Eralp (Case Reports in Orthopedics)
We present a 46-year-old female patient who is diagnosed with synchronous postirradiation sarcoma, cutaneous relapse of a previous soft tissue sarcoma, and lung adenocarcinoma. More than one malignant tumor at the same time with an accompanying relapse of a previous malignant tumor is a rare entity. A relatively young patient diagnosed with adenocarcinoma of the urethra before age 40, which is an unusual tumor for that age, later three more different malignant tumors being diagnosed, two of which are synchronous, causes the suspicion of Li-Fraumeni syndrome.